The relative age effect and its influence on athletic performance in Chinese junior female` tennis players - Aku, Y.; Yang, C. (PLOS ONE, 2024)
The relative age effect (RAE) has been the focus of numerous studies; however, there are still fewer studies in women`s sports than in men`s sports. In this study, all female players (N = 2,255) who participated in Chinese junior tennis competitions (U12, U14, U16, and the National Junior Team) from 2014 to 2019 were investigated in terms of competitors` birth dates and year-end rankings. For the purposes of the analysis, the birth dates were also separated into quarters and half years. The study`s objectives were to analyze the prevalence of the RAE among young Chinese female tennis players and to further examine how the RAE affects athletic performance. Differences between the observed and expected distributions of birth dates were tested using the chi-square statistic, and subsequent calculations were tested using odds ratios. The RAE was discovered to be present in every group of Chinese junior female tennis players (p < 0.001), with the proportions of those born in the first half of the year being 56.4% (U12), 53.1% (U14), and 57.0% (U16), respectively. The RAE for athletes selected for the National Women`s Junior Tennis Team was even more significant, with the percentage of birth dates in the first half of the year at 61.2%. Finally, we observed a tendency for the effect of the RAE on the athletic performance of adolescent female tennis players to diminish with age.